Mobilization of Chimeric oriT Plasmids by F and R100-1: Role of Relaxosome Formation in Defining Plasmid Specificity - Fekete, Richard A. (American Society for Microbiology, 2000)
Cleavage at the F plasmid nic site within the origin of transfer (oriT) requires the F-encoded proteins TraY and TraI and the host-encoded protein integration host factor in vitro. We confirm that F TraY, but not F TraM, is required for cleavage at nic in vivo. Chimeric plasmids were constructed which contained either the entire F or R100-1 oriT regions or various combinations of nic, TraY, and TraM binding sites, in addition to the traM gene. The efficiency of cleavage at nic and the frequency of mobilization were assayed in the presence of F or R100-1 plasmids. The ability of these chimeric plasmids to complement an F traM mutant or affect F transfer via negative dominance was also measured using transfer efficiency assays. In cases where cleavage at nic was detected, R100-1 TraI was not sensitive to the two-base difference in sequence immediately downstream of nic, while F TraI was specific for the F sequence. Plasmid transfer was detected only when TraM was able to bind to its cognate sites within oriT. High-affinity binding of TraY in cis to oriT allowed detection of cleavage at nic but was not required for efficient mobilization. Taken together, our results suggest that stable relaxosomes, consisting of TraI, -M, and -Y bound to oriT are preferentially targeted to the transfer apparatus (transferosome).